No Connection between Long-Term Lithium Treatment and Antithyroid Antibodies - Kraszewska, Agnieszka; Ziemnicka, Katarzyna; Sowiński, Jerzy; Ferensztajn-Rochowiak, Ewa; Rybakowski, Janusz K. (Pharmacopsychiatry, 2019)
Introduction The studies on the effect of lithium treatment on antithyroid antibodies showed either a higher concentration of these antibodies in patients receiving lithium compared to those lithium-naive or no difference between these groups. In lithium-treated bipolar patients, some researchers pointed to an association between antithyroid antibodies and other features of thyroid dysfunction such as hypothyroidism and decrease of glomerular filtration rate.Methods We compared antithyroid antibodies in 98 patients (30 male, 68 female) with bipolar disorder, aged 62±13 years, who received lithium for 19±10 years to 39 patients (12 male, 27 female), aged 57±10 years, who were never treated with lithium. The antibodies against thyroid peroxidase (TPOAb), against thyroglobulin (TGAb), and thyroid-stimulating hormone (TSH) receptors (TSHRAb) were estimated.Results No difference in the percentages of antibodies occurrence was found between groups, although the concentrations of TGAb were higher in patients receiving lithium. In lithium-treated patients, the presence of TPOAb was associated with lower concentrations of free triiodothyronine and the presence of TGAb, with higher concentrations of TSH. In females, the levels of TGAb were associated with lower thyroid volume. The concentrations of TPOAb correlated positively with the duration of lithium therapy in males, and those of TPOAb and TGAb negatively, with such duration, in female patients.Conclusion The results obtained showed no significant connection between long-term lithium treatment and antithyroid antibodies. In bipolar patients receiving lithium longitudinally, antithyroid antibodies can be associated with some indexes of thyroid function. However, they behave differently in male and female patients.
Keywords: bipolar disorder; lithium; antithyroid antibodies